1992
DOI: 10.1017/s1742758400013618
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of tomato varieties to the tomato russet mite, Aculops lycopersici (Massee) (Acarina: Eriophyidae)

Abstract: There were significant differences in the level of susceptibility among the 12 varieties which were screened for resistance to A. lycopersicL Pronounced tolerance to leaf damage was recorded on varieties Early Stone Improved and Beauty. Oxheart and Bonny Best both of which had comparatively lower mite densities were highly susceptible. Flower bud formation was not significantly affected by the mite damage. However, the number of dead flowers and flower buds on infested plants was significantly more than on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…However, Grande and H2274 had lower mite population densities. These findings are consistent with other studies that reported differences among tomato cultivars/accessions or wild tomato species infested with A. lycopersici (Kamau et al, 1992;Leite et al, 2000;Kitamura and Kawai 2006;Wang et al, 2008). Under natural conditions, the A. lycopersici density reached its highest yearly population from mid-August to mid-September, when the mean temperature and relative humidity were 25.6°C and 60.9%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…However, Grande and H2274 had lower mite population densities. These findings are consistent with other studies that reported differences among tomato cultivars/accessions or wild tomato species infested with A. lycopersici (Kamau et al, 1992;Leite et al, 2000;Kitamura and Kawai 2006;Wang et al, 2008). Under natural conditions, the A. lycopersici density reached its highest yearly population from mid-August to mid-September, when the mean temperature and relative humidity were 25.6°C and 60.9%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…(Rust) mites, thrips and other sucking insects [107][108][109], mechanical damage by wind, hail, contact with branches [110,111] Zineb against citrus mites [108,109,112] Prune On immature fruit: longitudinal stripes at stylar end [113], mature: rough, brown, dried surface [113] Copper spray [113], mechanical damage by wind, abrasion by leaves, shoots, adjacent fruits [113,114], exposure to surface wetness or free water, high humidity [113,114], scab [115] Captafol, ziram for scab control [113] Loquat Deep brown stripes, approx. 1 mm wide [116,117] Growth stress [116,117], microclimate (high temperature) [116], very high light intensities [116] Shading using nets to decrease growth rate during cell division phase [116,118] Tomato Russet as rough corky discolored surface [119], also referred to as 'shoulder check' [119] or 'cuticle cracking' [120] Rust mites [71,121], growth stress [120,122,123], surface moisture [119] Non-susceptible cultivars [123], moderate thinning [123], spray application of Ca+B [119,124] Melon Rind netting common in some cultivars [14], russet as dry, white to brownish ridges [14] Growth stress …”
Section: Applementioning
confidence: 99%
“…Pests and diseases may cause russeting in several fruitcrops. Examples of such pests include the citrus rust mite [107][108][109] and the tomato rust mite [71,121]. Similarly, fungi, such as powdery mildew in apple or epiphytic yeast species in apple and pear, have been reported to be causal in russeting (Table 1).…”
Section: Factors In Russet Formationmentioning
confidence: 99%
“…potato, eggplant and petunia. Significant differences in susceptibility to A. lycopersici were found between tomato varieties 10 and highly resistant allied species of the same genus as tomato were found (Kitamura & Kawai, unpublished). Breeding of resistant varieties is expected.…”
Section: Damage To Tomato Plantmentioning
confidence: 99%